2016
DOI: 10.1002/pip.2840
|View full text |Cite
|
Sign up to set email alerts
|

Radiation degradation characteristics of component subcells in inverted metamorphic triple-junction solar cells irradiated with electrons and protons

Abstract: The radiation response of In 0.5 Ga 0.5 P, GaAs, In 0.2 Ga 0.8 As, and In 0.3 Ga 0.7 As single-junction solar cells, whose materials are also used as component subcells of inverted metamorphic triple-junction (IMM3J) solar cells, was investigated. All four types of cells were prepared using a simple device layout and irradiated with high-energy electrons and protons. The essential solar cell characteristics, namely, light-illuminated current-voltage (LIV), dark current-voltage (DIV), external quantum efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 23 publications
(28 reference statements)
1
40
0
Order By: Relevance
“…However, these deviations still remain within our estimated error. As expected by the literature, the tested cells are more sensitive to the irradiation dose than to the particle energy(): Congruently, we observe that the arising of a middle‐limited regime in EOL2 sample is fundamentally due to the employed high dose, which is more intense with respect to the case of EOL1 sample, rather than the kind and energy of the involved particles, as pointed out in previous studies. ()…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…However, these deviations still remain within our estimated error. As expected by the literature, the tested cells are more sensitive to the irradiation dose than to the particle energy(): Congruently, we observe that the arising of a middle‐limited regime in EOL2 sample is fundamentally due to the employed high dose, which is more intense with respect to the case of EOL1 sample, rather than the kind and energy of the involved particles, as pointed out in previous studies. ()…”
Section: Resultssupporting
confidence: 83%
“…() For these reasons, handling the peculiar multijunction current limitation effect requires that the 3J InGaP/InGaAs/Ge spatial devices are generally tailored in the so‐called top‐limited configuration, so that each middle and bottom cell supplies current levels higher than the top one: Then the final current of the cell is limited by the current produced by the top subcell. () Nevertheless, very high irradiation conditions can deteriorate the middle cell more than the other ones, so much that the response of the whole device is changed into a middle‐limited configuration, strongly affecting the final performance. ()…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific previous studies on irradiated thick CTJ30 solar cells demonstrated that the introduction of this Bragg structure is able to increase the performance of the solar cell both in BOL and EOL conditions. The irradiation damage were evaluated by calculating the remaining factors, a figure of merit specifically employed in these kind of studies [22]. Indeed, the qualification campaign highlighted very good resistance under electron and proton irradiation [23].…”
Section: Sample Featuresmentioning
confidence: 99%
“…Therefore, Equation is no longer strictly valid. Taking in addition a linear increase of the back‐surface recombination velocity with DDD into account, the observed linear dependence can be rationalized.…”
Section: Displacement Damage Dose Analysismentioning
confidence: 99%